Enhanced heat transfer in parabolic trough using novel perforated plus-shaped turbulator - Attia Boudjemline; Ali B.M. Ali; S.A.M. Mehryan; A.I. Ismail; Ibrahim Mahariq; Nidhal Ben Khedher (Case Studies in Thermal Engineering)
Enhancing the thermal performance of parabolic trough solar collectors (PTSCs) is critical for developing efficient solar energy systems. Traditional PTSCs use circular absorber tubes, which limit heat transfer due to poor fluid mixing. This study introduces a novel flat absorber tube with a plus-shaped twisted turbulator (PSTT) to improve performance. The PSTT induces swirling flows, enhancing fluid mixing and reducing thermal resistance. Two PSTT configurations—simple and perforated—are evaluated, with variations in pitch lengths (160–20 mm), clearances (0.75–0.05 mm), and hole diameters (1–5 mm). A three-dimensional computational fluid dynamics model, using the RNG k-ε turbulence model coupled with the energy equation, analyzes thermal and hydraulic performance. Results show that the flat tube alone increased the heat transfer rate by 43.9 % compared to a standard circular tube, with a 67 % increase in pressure drop, yielding a 21.1 % improvement in the thermal performance factor (TEF). Incorporating the PSTT further improves performance, with the optimal configuration (pitch: 40 mm, clearance: 0.05 mm, hole diameter: 4 mm) achieving a maximum TEF of 2.7. These findings highlight the flat absorber tube with PSTT as a promising design for significantly enhancing PTSC thermal efficiency, paving the way for advanced solar thermal systems.